An improved component carrier selection algorithm for downlink long term evolution advanced - Mohd. Ramli, Huda Adibah; Mohd. Isa, Farah Nadia; Asnawi, Ani Liza (Institute of Electrical and Electronics Engineers Inc., 2014)
Long Term Evolution-Advanced (LTE-A) supports much wider transmission bandwidth through Carrier Aggregation (CA). CA is a method that aggregates multiple Component Carriers (CCs) of the same or different frequency bands. Additionally, LTE-A system needs to simultaneously support a mixture of LTE-A and Long Term Evolution (LTE) users. The LTE-A users can transmit on multiple CCs whereas the LTE users are restricted to transmit on a single CC. Given that there are multiple CCs available, an efficient CC selection algorithm is necessary in order to assign a CC to each LTE user. This paper proposes a novel CC selection algorithm to efficiently utilize the available radio resources whilst balancing total load across multiple CCs. Results obtained via simulation have demonstrated the efficacy of the proposed algorithm in optimizing the system capacity without compromising the Quality of Service (QoS) requirements of delay-sensitive Guaranteed Bit Rate (GBR) application.